2020
DOI: 10.1038/s41598-020-75301-4
|View full text |Cite
|
Sign up to set email alerts
|

Activation of toll like receptor 4 (TLR4) promotes cardiomyocyte apoptosis through SIRT2 dependent p53 deacetylation

Abstract: Cardiomyocyte inflammation followed by apoptosis and fibrosis is an important mediator for development and progression of heart failure. Activation of toll-like receptor 4 (TLR4), an important regulator of inflammation, causes the progression of cardiac hypertrophy and injury. However, the precise mechanism of TLR4-mediated adverse cardiac outcomes is still elusive. The present study was designed to find the role of TLR4 in cardiac fibrosis and apoptosis, and molecular mechanism thereof. Rats were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 37 publications
4
44
0
Order By: Relevance
“…Definitive support can be found in the same study, as the use of zZad-fmk (a general caspase inhibitor) inhibited the cytotoxic effect of Microcin. Caspase 3 activation has been linked to the activation of TLR-4 [ 36 ], therefore we are confident in our conclusion that Microcin must bind to TLR-4. Caspase 1 activation has been linked to the efflux of potassium ions, which activates the NLRC4 (nucleotide-binding oligomerization domain and leucine-rich repeat containing receptors) inflammasome pathway leading to the assembly of caspase 1 [ 37 ].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Definitive support can be found in the same study, as the use of zZad-fmk (a general caspase inhibitor) inhibited the cytotoxic effect of Microcin. Caspase 3 activation has been linked to the activation of TLR-4 [ 36 ], therefore we are confident in our conclusion that Microcin must bind to TLR-4. Caspase 1 activation has been linked to the efflux of potassium ions, which activates the NLRC4 (nucleotide-binding oligomerization domain and leucine-rich repeat containing receptors) inflammasome pathway leading to the assembly of caspase 1 [ 37 ].…”
Section: Discussionsupporting
confidence: 52%
“…Divercin has previously been shown to have a similar homology to Pediocin whilst showing no anti-tumour properties towards HT29 cells [ 36 ]. Therefore, we performed sequence alignment and 3D modelling of Divercin V41 in order to try and understand why, despite the similar homology, one shows anti-tumour effects towards HT29 cells and not the other.…”
Section: Resultsmentioning
confidence: 99%
“…At present, TLR4 has been identified as a crucial regulator in cardiovascular disease. Studies have found that TLR4 activation in rats promotes cardiac inflammation, mitochondrial dysfunction, apoptosis and fibrosis [ 59 , 60 ]. In addition, the "glutamate receptor pathway" and "calcium ion pathway" were often identified in GO and KEGG analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of SIRT2 can inhibit the acetylation of p53 and thus inhibit the damage of TLR4 to cardiomyocytes. 39 The reason why SIRT2 has these two opposite functions needs further research to discover.…”
Section: Sirt2 and Heart‐related Diseasesmentioning
confidence: 99%